IDEOLOGI RADIKALISME DALAM ISLAM TENTANG WACANA HOMOSEKSUAL DI MEDIA MASSA - Fita Fathurokhmah (INJECT (Interdisciplinary Journal of Communication), 2018)
This article wants to examine how the media ideology about the concept of radicalism in Islam in the mass media of Republika and Koran Tempo. The Republika newspaper supports and agrees to the Islamic Defenders Front (FPI) both with an understanding of the prohibition of homosexuality and the appointment of news of FPI's violence against homosexuals. The Tempo newspaper is more about renewing ideas such as reporting on the views of the Liberal Islam Network (JIL) in respect of homosexuals. Homosexuality is the same sex lover or the choice of sexuality abnormalities is normal as a human being, it does not need to be criticized but must be respected as individual freedom. There is a fundamental ideological difference between Republika and Koran Tempo by renewing the concept of homosexuality with thinking radicalism on the basis of Islamic teachings. The homosexual issue, FPI applies the meaning of Islamic radicalism from the right-wing side which promotes violence as resistance, while JIL applies the meaning of radicalism from the left-wing side which prioritizes the radicalism of thought and law in the Koran.  AbstrakArtikel ini ingin mengkaji bagaimana ideologi media tentang konsep radikalisme dalam Islam di media massa Republika dan Koran Tempo. Surat kabar Republika mendukung dan setuju pada Front Pembela Islam (FPI) baik dengan pemahaman pelarangan homoseksual dan pengangkatan berita tindak kekerasan FPI melawan homoseksual. Koran Tempo lebih pada pembaharuan pemikiran seperti pemberitaan pandangan Jaringan Islam Liberal (JIL) terkait menghormatinya kaum homoseksual. Homoseksual adalah penyuka sesama jenis atau pilihan kelainan seksualitas itu normal sebagai manusia, tidak perlu dicela tapi harus dihargai sebagai kebebasan individu. Terdapat perbedaan ideologi yang mendasar antara Republika dan Koran Tempo dengan melakukan pembaharuan konsep homoseksual dengan radikalisme berpikir dengan pijakan ajaran Islam. Persoalan homoseksual, FPI menerapkan makna radikalisme Islam dari sisi sayap kanan yang mengedepankan kekerasan sebagai perlawanan, sedangkan JIL menerapkan makna radikalisme dari sisi sayap kiri yang mengutamakan keradikalan pemikiran dan hukum dalam al-Quran.